2021
DOI: 10.1101/2021.12.08.471814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanotrap Particles Improve Nanopore Sequencing of SARS-CoV-2 and Other Respiratory Viruses

Abstract: Presented here is a magnetic hydrogel particle enabled workflow for capturing and concentrating SARS-CoV-2 from diagnostic remnant swab samples that significantly improves sequencing results using the Oxford Nanopore Technologies MinION sequencing platform. Our approach utilizes a novel affinity-based magnetic hydrogel particle, circumventing low input sample volumes and allowing for both rapid manual and automated high throughput workflows that are compatible with nanopore sequencing. This approach enhances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This capability has been demonstrated with Nanotrap particles used in a coinfection scenario with HIV and Rift Valley Fever Virus in bovine serum [12] . Since the COVID-19 pandemic began, Nanotrap particles have been used to detect SARS-CoV-2 [14, 15] and other respiratory viruses [16, 17] in wastewater. For example, Anderson et al [17] demonstrated that Nanotrap particles can be used for simultaneous concentration and detection of SARS-CoV-2, influenza, and Respiratory Syncytial Virus in wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…This capability has been demonstrated with Nanotrap particles used in a coinfection scenario with HIV and Rift Valley Fever Virus in bovine serum [12] . Since the COVID-19 pandemic began, Nanotrap particles have been used to detect SARS-CoV-2 [14, 15] and other respiratory viruses [16, 17] in wastewater. For example, Anderson et al [17] demonstrated that Nanotrap particles can be used for simultaneous concentration and detection of SARS-CoV-2, influenza, and Respiratory Syncytial Virus in wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…This capability has been demonstrated with Nanotrap particles used in a coinfection scenario with HIV and Rift Valley fever virus in bovine serum (Shafagati et al, 2013 ). Since the COVID-19 pandemic, Nanotrap particles have been used to detect SARS-CoV-2 (Karthikeyan et al, 2021a , b ; Zhan et al, 2022 ; Ahmed et al, 2023 ) and other respiratory viruses (Shafagati et al, 2016 ; Anderson et al, 2021 ) in wastewater. For example, Anderson et al ( 2021 ) showed that Nanotrap particles can be used for the concentration and detection of SARS-CoV-2, influenza, and respiratory syncytial viruses in wastewater simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…A48383) using the automated nucleic acid extractor KingFisher™ Apex Magnetic Particle Processor. The protocol was completed as described previously 7 . The RT‐PCR analyses were performed using the TaqPath COVID‐19 CE‐IVD RT‐PCR Kit (Life Technologies, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The disease transmission dynamics and the pandemic progression within many African countries, including Angola, are still not investigated in detail. Angola lacks a strong genomic surveillance network, despite the emergence of two variants of concern (VOCs) within the southern African region, 6,7 and outbreaks of reemerging infectious diseases 8–11 . This may hamper the timely detection and early warning of newly emerging VOCs, variants of interest (VOIs), and other outbreaks of infectious diseases of global importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation